Television in the Age of Radio: Modernity, Imagination, and the Making of a Medium - PHILIP W. SEWELL (Rutgers University Press, 2014)
This book explores the very real impact that language and culture have on our world and how we live in it, taking as its case study the role that imagination played in effecting television as a technology, industry, and medium in the United States. In particular, it focuses on the ways in which culture shaped the understandings of and aspirations for television in the period from the mid- 1920s to the late 1940s. Those knowledges and hopes matter not only because they worked to coordinate a host of human activities that were crucial to the development of television but also because they demonstrate some of the ways in which people made sense of and a place for themselves in industrialized modernity. Writing about television became a mode of public thought and speculation about intersecting systems of capital, gadgets, values, and power that not only worked to define or dispute television as a technology or industry or system of communication but also projected cultural concerns from one seemingly distinct domain of thought onto another. For instance, later in Gernsback’s editorial he uses the example of being able to see opera or the president as an index of the medium’s significance, thereby setting aesthetic and political goals for a technology that could not yet achieve them, while imagining television’s users as people with serious tastes and interests. This was not random. Discourses of evaluation and systems of authority for talking and thinking about television were fashioned from a range of earlier habits of thought and allocations of cultural power in order to articulate a notion of what television should be.